Validation of a new NGS-based myeloid panel in acute myeloid leukemia: A single-center experience. (July 2022) - Steidl, Carolina; Aroldi, Andrea; Mologni, Luca; Crespiatico, Ilaria; Fontana, Diletta; Mastini, Cristina; Fumagalli, Monica; Perfetti, Paola; Borin, Lorenza; Valentini, Claudia; Piazza, Rocco; Gambacorti-Passerini, Carlo
Abstract: Acute myeloid leukemia (AML) identifies a heterogeneous group of clonal disorders, both clinically and genetically. A large number of mutations have been described in AML, although only a few are currently employed in clinical practice. Next generation sequencing (NGS) allows for better understanding of the complex genetic background in AML and may direct individualized therapies. In this study, we aim to identify molecular aberrations that are not routinely investigated in AML using an NGS-based panel encompassing 101 genes and to evaluate how their oncogenic potential correlates with survival. Forty consecutive patients with newly diagnosed AML were enrolled between January 2018 and April 2020. We performed targeted NGS and detected 96 mutations in 36 patients (90%), while 14 fusion genes were detected in 13 patients (32%). Each mutation was weighed using OncoScore, a text-mining tool ranking genes according to their oncogenic potential. An OncoScore ≥ 100 was associated with shorter PFS among our patients (p = 0.05). In 11 patients with no available MRD markers at diagnosis, we were able to perform NGS-based MRD monitoring using targeted deep sequencing. Overall, our study shows that NGS is a powerful tool in AML and should be employed both in routine diagnostic workup and follow up. Highlights: A large number of mutations have been described in AML, although only a few are routinely employed in clinical practice. We performed targeted NGS on 40 patients with AML using a new panel encompassing 101 genes. NGS detected 96 mutations, 12 of which deemed "actionable". Each mutation was weighed using OncoScore, a text-mining tool that ranks genes according to their oncogenic potential. An Oncoscore ≥100 was associated with shorter PFS in our cohort (p = 0.05).